2020
DOI: 10.1002/lary.29005
|View full text |Cite
|
Sign up to set email alerts
|

Speech Performance after Anterolateral Thigh Phonatory Tube Reconstruction for Total Laryngectomy

Abstract: Objective: Traditionally, after total laryngopharyngectomy (TLP), patients cannot speak without a prosthesis or an artificial larynx. In Taiwan, most patients use a commercialized pneumatic laryngeal device (PLD). Phonatory tube reconstruction with the anterolateral thigh (ALT) flap is a novel, modified version of synchronous digestive and phonatory reconstruction involving a free muscular cutaneous flap. This study reviewed and compared speech performance between patients who underwent novel flap reconstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Likewise, the development and refinement of novel reconstructive techniques including the anterolateral thigh phonatory tube have the potential to alleviate the costs of long-term maintenance, although at the expense of increasing upfront operative or hospital costs. 19 As the definitions of health care value shift toward patientcentered models, state insurers and policymakers should be urged to revisit coverage details given the impact of postlaryngectomy communication on quality of life. 3,4 The influence of psychosocial factors on speech outcomes is complex and inadequately studied.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the development and refinement of novel reconstructive techniques including the anterolateral thigh phonatory tube have the potential to alleviate the costs of long-term maintenance, although at the expense of increasing upfront operative or hospital costs. 19 As the definitions of health care value shift toward patientcentered models, state insurers and policymakers should be urged to revisit coverage details given the impact of postlaryngectomy communication on quality of life. 3,4 The influence of psychosocial factors on speech outcomes is complex and inadequately studied.…”
Section: Discussionmentioning
confidence: 99%
“…In the reconstruction of total laryngectomy, our study found that the ALT flap was more reliable than the peroneal flap. ALT flaps have a large skin donor site, dependable perforators, and adequate volume to fill the dead space and are simple to design with a monitor flap and phonatory tube 25,29 . The multilayer fascial underlay technique can also be used to reduce the rate of fistula formation even further 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the J-flap technique, first described by Tsao in 2020 [14], exploits a similar mechanism to TEP, i.e., the tracheoesophageal fistula, without the need for a voice prosthesis as the J tube conformation acts as a valve itself. This technique has already been proved to have satisfactory vocal results [11], but comparisons with the gold standard voice restoration method TEP have never been conducted. This study was designed to comprehensively assess various aspects of the voice rehabilitation outcome: the patients' subjective perception of their voice (VHI) and QoL (UW-QoL), the professional assessment by speech pathologists (GIRBAS, speech intelligibility and speech accuracy) and the objective evaluation of phonatory and acoustic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…We asked the patients to produce a sustained vowel, namely, /a/, at a conversational pitch and loudness. The instrument analyzed the voice produced to calculate the fundamental frequency (F0), jitter, shimmer and harmonic-tonoise ratio (HNR) [11].…”
Section: Acoustic Voice Analysismentioning
confidence: 99%
See 1 more Smart Citation